The effects of baseline strength, muscle size and body fat on individual responsiveness to resistance training - Nikkinen, Aki (2025)
Nikkinen, A. 2025. The effects of baseline strength, muscle size and body fat on individual responsiveness to resistance training. Faculty of Sport and Health Sciences, University of Jyväskylä, master’s thesis in exercise physiology, 41 pp.